Effect Of Light Environment On Harvest Quality And Postharvest Behavior Of Minimally Processed Sweet Pepper - Frezza, Diana; Miquel, Aina M. Pons; Logegaray, Veronica; Leon, Adrian P.; Chiesa, D., Angel (European Scientific Journal, ESJ, 2016)
The aim of this study was to evaluate the effect of two light environments on two maturity stages of sweet pepper and the postharvest behavior of minimally processed product using passive modified atmosphere. The size and fruit morphology were measured at harvest. Overall visual quality, gas concentration inside the bags, weight loss, soluble solids, firmness, electrolyte leakage, carotenoids and ascorbic acid were determined during the storage period. Results showed that quality parameters were affected by radiation and processing. Shaded pepper fruits showed higher water content and lower size compared to fruits exposed to full radiation. Fruit nutritional value was maintained, but after six days was not marketable. Visual quality of intact fruit was not affected without differences between treatments. Shelf life processed red fruits as julienne was reduced, being the worst performing during storage. Post-harvest visual quality was in relation to gases composition (O2 and CO2) inside the trays.